Trojan Horse Protest at Pashayan/Stockman Dinner At Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Adam Watkins looking at face of Trojan Horse while on shoulders of Howard Watkins Sign in background: "Freeze Nuclear War"